Financial analysis of GlaxoSmithKline Bangladesh Ltd.: a guideline for potential shareholders - Saeem, Abu Shalah Md. Shake (2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.